Dietary sodium acetate (SA) improves the growth performance, intestinal health, and carbohydrate metabolism of juvenile common carp (Cyprinus carpio) - Junchang Feng; Wenshan Cui; Shasha Liu; Xiaobei Liu; Zhongliang Cai; Xulu Chang; Xiao Yan; Shikun Feng; Jianxin Zhang; Guoxing Nie (Aquaculture Reports, 2022)
This experiment investigated the effects of dietary sodium acetate (SA) on the growth performance, intestinal health, and carbohydrate metabolism of juvenile Cyprinus carpio L. Four experimental diets were evaluated, including diets supplemented with 0.5 %, 1.0 % and 1.5 % SA and a control diet without supplementation. Triplicate repetitions (n = 30) of common carp (initial weight of 17.24 ± 0.40 g) per group were fed the respective diets for 8 weeks. Dietary SA significantly improved final weight, specific growth rate (SGR), weight gain (WG) and condition factor (CF) and a lower feed conversion ratio (FCR) compared to control group (P < 0.05). The viscera-somatic index (VSI) and survival rate (SR) were not significantly different (P > 0.05). For intestinal health, dietary SA significantly promoted digestive enzyme activities, including amylase, lipase and protease, and increased villus length and muscle thickness. With respect to carbohydrate metabolism, dietary SA significantly decreased blood glucose levels and hepatopancreas glycogen content, downregulated sglt1 and gult2 gene expression in the intestine (P < 0.05), and increased muscle glycogen content in comparison to the control group. In addition, dietary SA increased expression of glucose-6-phosphatase (g6pase) and phosphoenolpyruvate kinase (pepck) in gluconeogenesis, pyruvate kinase (pk) and glucokinase (gk) in glycolysis, and glucose transporter gult2 in the hepatopancreas (P < 0.05) but decreased expression of glycogen phosphorylase (pygl) in glycogenolysis and glycogen synthase (gys) in glycogen synthesis (P < 0.05). Overall, these findings indicate that dietary SA improves growth performance, intestinal health and carbohydrate metabolism, and that SA may potentially be used as a feed additive for common carp. According to the results, dietary 1.0 % SA is recommended for the formulation of common carp feed.